THE COMPARISON OF BERNSTEIN TEST RESULTS WITH ENDOSCOPIC AND HISTOPATHOLOGIC EXAMINATION IN PATIENTS WITH GASTROESOPHAGEAL REFLUX DISEASE (GERD). - Mustafa GÜLŞEN; Kemal DAĞALP; A. Kemal GÜRBÜZ; Necmettin KARAEREN; Can UYGURER; Sait BAĞCI; A. ALPER (Turkish Journal of Gastroenterology, 2020)
-